THE USAGE OF A-J+3+6 METHOD IN BRAILLE WRITING WITH SLATE AND STYLUS (Proceedings of International Conference on Special Education, 2017)
The purpose of this study is to compare the effectiveness of Braille writing with slate and stylus the conventional method and the A-J+3+6 method. The authors conducted an experimental study at the cluster primary school for the blind; eighteen blind and visually impaired (BVI) students from Year 2 and Year 3. Ten blind students and eight low vision students were selected as samples. A modified method of braille writing using slate and stylus derived from the abkl method and Mangold method namely A-J+3+6 method was used in this mix-method study. The qualitative data of focus group interview and observations were used to support the quantitative findings. Data analysis showed that method A-J+3+6 (M=76.11 SD=17.81) is more effective in braille writing using slate and stylus rather than the conventional method (M=46.67, SD=24.6) is statistically significant at the 0.05 level (t=2.907, p0.05).Braille Writing; Slate and Stylus; Blind and Visually Impaired